Identifikasi Mikroorganisme Rizosfer Tanaman Rambutan (Nephelium lappaceum) di Kabupaten Kutai Kartanegara, Kalimantan Timur - Purwati Purwati; Tutik Nugrahini (Universitas Widya Gama Mahakam, 2017)
One of the obstacles in increasing and stabilizing crop production is the onslaught of soil pathogens that causes damage to plants and decreases the quantity and quality of production. This study aims to identify and determine the population of rhizosphere microorganisms in rambutan plants. The research was conducted at Plant Pest and Disease Laboratory of Agricultural Faculty of Mulawarman University of Samarinda from July to August 2016. This research uses exploration method with observation technique which is done by growing microorganism in media so that for 5 days then calculate growth rate of each microorganism. The data obtained were analyzed using quantitative descriptive analysis. Based on the result of the research, it can be concluded that the results of isolation of micorganism from rhizosphere rambutan plant obtained 3 isolates include: 1 isolate bacteria from Azotobacteraceae Family and 2 isolates of fungi from genus Aspergilus and Phytium genus. Of the 3 types of isolates, 2 types of microorganisms are included into microorganisms that are beneficial to soil ecosystems that include the Azotobacteraceae Family that play a role in the fixation (fixation) N2 (biofertilizer) and Aspergillus Genus that act as a potential pathogen growth inhibitor (bio control) diseases in plants while the Phytium Genus is a pathogenic fungus (the cause of disease) that can affect the low production of plants.